A simple technique to improve the resolution of membrane acidic proteins of the haloarchaeon Haloferax volcanii by 2D electrophoresis - Paggi, Roberto Alejandro (2014)
Proteins present in the archaeal cell envelope play key roles in a variety of processes necessary for survival in extreme environments. The haloarchaeon Haloferax volcanii is a good model for membrane proteomic studies because its genome sequence is known, it can be genetically manipulated, and a number of studies at the “omics” level have been performed in this organism. This work reports an easy strategy to improve the resolution of acidic membrane proteins from H. volcanii by 2DE. The method is based on the solubilization, delipidation, and salt removal from membrane proteins. Due to the abundance of the S-layer glycoprotein (SLG) in membrane protein extracts, other proteins from the envelope are consequently underrepresented. Thus, a protocol to reduce the amount of the SLG by EDTA treatment was applied and 11 cm narrow range pH (3.9–5.1) IPG strips were used to fractionate the remaining proteins. Using this method, horizontal streaking was substantially decreased and at least 75 defined spots (20% of the predicted membrane proteome within this pI/Mw range) were reproducibly detected. Two of these spots were identified as thermosome subunit 1 and NADH dehydrogenase from H. volcanii, confirming that proteins from the membrane fraction were enriched. Removal of the SLG from membrane protein extracts can be applied to increase protein load for 2DE as well as for other proteomic methods.